NSOAS24: a new global marine gravity model derived from multi-satellite sea surface slopes - S. Zhang; X. Chen; R. Zhou; Y. Jia (Geoscientific Model Development)
Judging by the early release of the NSOAS22 model, there were some known issues, such as boundary connection problems in blockwise solutions and a relatively high noise level. By solving these problems, a new global marine gravity model, NSOAS24, is derived based on sea surface slopes (SSSs) from multi-satellite altimetry missions. Firstly, SSSs and along-track deflections of vertical (DOVs) are obtained by retracking, resampling, screening, differentiating, and filtering procedures on the basis of altimeter waveforms and sea surface height measurements. Secondly, DOVs with a 1′×1′<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="32pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="aa61a3a75e7abd89c60a16c9d4958643"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gmd-18-1221-2025-ie00001.svg" width="32pt" height="12pt" src="gmd-18-1221-2025-ie00001.png"/></svg:svg> grid interval are further determined using Green's function method, which applies directional gradients to constrain the surface, least-squares fit to constrain noisy points, and tension constraints to smooth the field. Finally, the marine gravity anomaly is recovered from the gridded DOVs according to the Laplace equation. Throughout the entire processing procedure, improvements in accuracy are expected for the NSOAS24 model due to the following changes, e.g., supplementing recent mission observations and removing old mission data, optimizing the step size during Green's function method, and special handling in nearshore areas. These optimizations effectively resolved the known issues of signal aliasing and the “hollow phenomenon” in coastal zones. Typical altimetry-derived marine gravity models are the DTU series released by the Technical University of Denmark and the S&S series released by the Scripps Institution of Oceanography (SIO), University of California San Diego (UCSD). Their latest models, DTU21 and SS V32.1, were used for comparison and validation. Numerical verification was conducted in three experimental areas (the Mariana Trench area, Mid-Atlantic Ridge area, and Antarctic area, representing low-, mid-, and high-latitude zones) with DTU21, SS V32.1, and shipborne data. Taking NSOAS22 for comparison, NSOAS24 showed improvements of 1.2, 0.7, and 1.0 mGal in the three test areas by validating with SS V32.1, while declines of 0.6, 0.5, and 0.3 mGal and 0.2, 0.4, and 0.3 mGal occurred in SD statistics with DTU21 and shipborne data. Finally, NSOAS24 was assessed using two sets of shipborne data (the early National Centers for Environmental Information (NCEI) dataset and the later dataset from the Japan Agency for Marine-Earth Science and Technology (JAMSTEC), the Marine Geoscience Data System (MGDS), the French Oceanographic Cruises Directory (FOCD), and the French Naval Hydrographic and Oceanographic Service (SHOM)) on a global scale. Generally, NSOAS24 (6.33 and 4.95 mGal) showed a comparable accuracy level with DTU21 (6.20 and 4.71 mGal) and SS V32.1 (6.40 and 5.53 mGal) and better accuracy than NSOAS22 (6.64 and 5.64 mGal). The new model is available at https://doi.org/10.5281/zenodo.12730119 (Zhang et al., 2024).